Molecular dynamics simulations of hydrogen diffusion behaviour at tungsten surface. (July 2014) - Liu, Yi-Nan; Yu, Yi; Shu, Xiaolin; Lu, Guang-Hong
Abstract : Tungsten (W) is considered to be a promising candidate for plasma facing materials in fusion reactors because of its high melting point, high thermal diffusivity and low sputtering yield. To investigate the multiple hydrogen (H) diffusion behaviours at the W(001) surface, molecular dynamics simulations were used to study the H distributions after diffusion of 1 ns under different conditions. The results of using different H concentrations and temperatures showed the preference of bulk to surface diffusion, and the H distribution patterns of the H/W ratio of 0·1 are analysed in detail with an 'empty' region near the surface. The effect of temperature on H diffusion is also investigated, which gives the highest adsorption peak at a mediate temperature of 900 K. The trapping effect of vacancies on H atoms is demonstrated at different vacancy concentrations. The effect of H embedded depth on H distribution is also investigated together with the effect of temperature, which gives an increasing trend of temperature with the highest adsorption peak with the H depth.